Effectiveness of Divorce Case Resolution through Mediation: Case Study at Boyolali Religious Court - Beta Amalia Nur Fajrin; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2025)
Mediation is a process that the parties must go through during the process of resolving a divorce case before the parties proceed with the case to the trial table. The parties must go through this mediation stage first. So, in an effort to increase the success of mediation, the Supreme Court implemented Supreme Court Regulation no. 1 of 2016 which contains related Mediation Procedures in Court. The research method that the author uses is a quantitative research method. By using data sources consisting of primary data, secondary data in the form of primary, secondary and tertiary legal materials, the primary data used in this research is data obtained directly from the field. The aim of this research is to understand the effectiveness of mediation in resolving divorce cases, and as evaluation material it is necessary to find out what can be supporting and inhibiting factors for the success of mediation. The results of research at the Boyolali Religious Court that mediation in resolving divorce cases has been effective is proven by the success rate of mediation in resolving divorce cases increasing in 2022 and 2024. However, there are still many factors that hinder the success of mediation, such as the strong desire of the parties to divorce, besides that there are also supporting factors in the form of family support for the parties to reconcile. Mediation in Divorce Cases at the Boyolali Religious Court has succeeded in reducing the divorce rate by 39.35% in 2024.